Analysis of the Death Penalty in the Context of Human Rights Law - Kadek Arya Putra Gunawan; I Nyoman Bagiastra (West Science Interdisciplinary Studies, 2023)
This research explores the implementation of the death penalty in Indonesia in the context of human rights through literature study methods. The fundamental problem lies in legal uncertainty, human rights violations, and social impacts arising from the execution of the death penalty. The purpose of the study is to analyze these complex dynamics with a focus on Indonesian conditions. The literature study method is used to investigate scientific works, human rights reports, and related official documents. The results showed policy changes, non-conformity to human rights standards, as well as shifts in public opinion and international responses. The conclusion of the study underscores the need for more progressive policy measures to ensure fairness, transparency, and protection of individual rights in the execution of the death penalty in Indonesia. The novelty of this research lies in its comprehensive approach to this controversial issue, offering an in-depth and relevant perspective for further understanding.